THE EFFECT OF THE PROBLEM BASED LEARNING MODEL ON SCIENCE PROBLEM SOLVING ABILITY AND SELF REGULATED LEARNING - Nyoman Ayu Putri Lestari; Made Sri Astika Dewi; Ni Putu Eni Astuti; Putu Gede Asnawa Dikta; Ni Putu Juni Artini; Made Padmarani Sudewiputri; Julhidayat Muhsam (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
The demands of 21st century education emphasize the importance of higher-order thinking skills (HOTS). One approach considered effective in supporting the achievement of these goals is the implementation of the Problem Based Learning (PBL) model. This study aims to evaluate the effectiveness of the PBL model in enhancing problem solving skills in science subjects and self regulated learning among elementary school students. The research employed a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of two classes, each serving as either the experimental or the control group. Data were collected using instruments in the form of a test to assess science problem solving ability and a questionnaire to measure self-regulation learning. The analysis using MANOVA revealed a significant effect of PBL implementation on the simultaneous improvement of both variables, with a significance level of 0.001, which is less than 0.05. These results indicate that PBL is capable of creating an active, reflective, and collaborative learning environment. The conclusion of this study affirms that PBL is an effective alternative instructional strategy for supporting students' holistic competency development. Therefore, it is recommended that this model be implemented more broadly in thematic learning at the elementary school level and further explored for development across different educational levels and contexts.